TEMBANG DAN MODEL PENGAJARANNYA - ., Bambang Sulanjari . (MALIH PEDDAS, 2011)
TEMBANG DAN MODEL PENGAJARANNYA Bambang Sulanjari4 Â Abstrak The major of Tembang is a small part of the constellation of the Java language curriculum that included in the clumps. Due to a less strategic position, this major is often overlooked, but if further explored, this major is so potential to develop the character of students. At least, tembang can be utilized most effectively to develop the four language skills: listening, reading, writing and speaking. Competencies can be developed in the tembang learning of them are the students able to sing the song, phrasing the song and make song. Learning model selection is crucial in the success of tembang learning. Creativity of teachers in selecting and implementing learning model is very influential on the success of tembang learning, therefore teachers must be creative to determine the model according to the circumstances. In terms of song selection of teaching methods, teachers can develop methods that are inherited ancestors, such as methods of learning with playing, the method of learning with moving, step by step method, and karaoke method.